CHANDIGARH: Le Corbusier and the new city in the Chilean culture, 1951-1957 - Horacio Torrent (Materia Arquitectura, 2013)
The article presents the way in which two Chilean cultural publications interpreted the building and design of Chandigarh. Through the building of the Indian city, the weekly publication Pro-Arte and the periodical Pomaire showed, in the 1950s, a different Le Corbusier from the one traditionally presented in the cultural architectural world. Away from abstraction and very related to practice, the urban theories of the Swiss maestro linked with the cultural tradition of India. In architecture, on the other hand, his approaches to climate and lifestyles were confirmed.